Acerca del problemade la transformación de Valores a Precios - Mora Plaza, Antonio (Nómadas. Critical Journal of Social and Juridical Science, 2010)
This paper treat about the problem originated in Marx with his III The Capital volume for to pass of value system of capitals to a prices system. Marx gave a mistake solution and Bortkiewicz gave the first good solution. This art. is a attempt to give the news solutions with some surprise and make discussion of the before.